Perpustakaan Tun Abdul Razak UiTM Digital Library : Open Access Discovery / Perpustakaan Tun Abdul Razak, Universiti Teknologi MARA - UiTM, Perpustakaan Tun Abdul Razak (Perpustakaan Tun Abdul Razak, 2020)
Open Access is an initiative of the Digital Collection services for materials produced by authors from all over the world that are accessible for free